A taxonomic revision of the Bothynus villiersi Endrödi, 1968 species group (Coleoptera: Scarabaeidae: Dynastinae) - Duarte, Paulo R. M.; Grossi, Paschoal C.; Dupuis, Fabien (Zootaxa, 2022)
The Bothynus villiersi species group (Coleoptera: Scarabaeidae: Dynastinae: Pentodontini) is revised and is composed of five South American species: Bothynus villiersi Endrödi, 1968; Bothynus horridus Endrödi, 1968; Bothynus alvarengai Martínez, 1983; Bothynus spinophallicus (Ratcliffe & Cave, 2021) new combination; and Bothynus belemensis new species. Redescriptions, illustrations, new diagnostic characters, identification key, and a first known geographical distribution map for the group are presented.